“Real presence” and sacramental praxis – Reformed reflections on the Eucharist - De Gruchy, John (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
As the subtitle indicates, this essay focuses on a Reformed understanding of the Eucharist or Sacrament of Holy Communion. After a brief introduction indicating why this topic is important today, the essay engages a number of key themes. First amongst these is the historical character of the sacrament which needs to be kept in tension with what Calvin referred to as its mystery. The second is the distinctly Reformed understanding of the relationship between Word, Spirit and Sacrament, and its implications for Eucharistic practice within reformed congregations. The third is the meaning and significance of the real presence of Christ in the Eucharist. This goes to the heart of the essay, for how this is understood is crucial for a proper Eucharistic theology and praxis. The essay argues that Calvin’s understanding of the real presence has generally been lost within Reformed circles and needs to be recovered if the Sacrament is to be restored to its rightful place.